Evolution of maritime logistics in the age of integrated supply chain management - Li, Qing. (2009)
Following the heritage of containerization, intermodality and transshipment, an era of integrated maritime logistics has come into the stage. Due to the influence of globa lization and lean manufacturing practices, the logistics framework has evolved from a supply-driven to a demand driven system. As a result, shipping lines are expected to perform a highly integrated, reliable, efficient and value-added package of services, through wearing themselves into shippers’ supply chain. Besides, this trend of maritime integration into third-party logistics (3PL) is also driven by other factors, such as attractive business potential, possible demand complementary, cost reductions and strengthened market power. However, maritime logistics is catching not only the attention of shipping lines but also the ones of port operators, freight intermediaries and alike. Research into the logistics industry has shown that shipping lines have a few advantages that can outshine the other players but they may also face some difficulties in the process. In order to succeed, shipping lines need to equip themselves with suitable strategies and wellorganized structures. Liners should adopt different development plans according to their company sizes and integration intentions. While ultimately, it depends on how the companies perceive the market and where they want to position themselves.